Exploring Gastronomy Tourism: A Cultural and Culinary Journey through Pasar Lama Tangerang - Ayuningsih, Sri Fajar; Amelia, Rizki; Adi, Antonius (Journal of Mandalika Review, 2025)
Introduction: Gastronomy tourism has a significant impact on enhancing historical traditions and promoting local culinary identities. Pasar Lama Tangerang, known for its rich Chinese-Betawi Peranakan cuisine, has become a significant gastronomic tourism destination that offers visitors an immersive cultural and culinary experience. This study seeks to examine the influence of Peranakan cuisine on the tourist experience in Pasar Lama Tangerang, using the framework of gastronomy tourism and cultural heritage theories. Methodology: Using a qualitative descriptive approach, this research employed triangulated data collection techniques including semi-structured interviews, participant observation, and digital content analysis. A purposive sample of 15 informants—comprising local vendors, cultural figures, and tourists respond were analyzed. Findings: The findings indicate that the diversity of Chinese-Betawi Peranakan cuisine in Pasar Lama Tangerang provides a unique and memorable experience for visitors, allowing them to engage with traditional dishes while also appreciating the historical and cultural narratives embedded in the culinary landscape. Conclusion: The research emphasizes the significance of preserving and enhancing traditional gastronomic traditions as a way of strengthening local tourism. These insights help expand the discussion on gastronomic tourism by highlighting the influence of culinary heritage in enhancing a destination's appeal.